Novel 4-alkoxy Meriolin Congeners Potently Induce Apoptosis in Leukemia and Lymphoma Cells - Karina S. Krings; Tobias R. Wassenberg; Pablo Cea-Medina; Laura Schmitt; Ilka Lechtenberg; Tanya R. Llewellyn; Nan Qin; Holger Gohlke; Sebastian Wesselborg; Thomas J. J. Müller (Molecules)
Meriolins (3-(pyrimidin-4-yl)-7-azaindoles) are synthetic hybrids of the naturally occurring alkaloids variolin and meridianin and display a strong cytotoxic potential. We have recently shown that the novel derivative meriolin 16 is highly cytotoxic in several lymphoma and leukemia cell lines as well as in primary patient-derived lymphoma and leukemia cells and predominantly targets cyclin-dependent kinases (CDKs). Here, we efficiently synthesized nine novel 2-aminopyridyl meriolin congeners (3a–3i), i.e., pyrimeriolins, using a one-pot Masuda borylation-Suzuki coupling (MBSC) sequence, with eight of them bearing lipophilic alkoxy substituents of varying length, to systematically determine the influence of the alkoxy sidechain length on the biological activity. All the synthesized derivatives displayed a pronounced cytotoxic potential, with six compounds showing IC50 values in the nanomolar range. Derivatives 3b–3f strongly induced apoptosis and activated caspases with rapid kinetics within 3–4 h in Jurkat leukemia and Ramos lymphoma cells. The induction of apoptosis by the most potent derivative 3e was mediated by the intrinsic mitochondrial death pathway, as it was blocked in caspase-9 deficient and Apaf-1 knockdown Jurkat cells. However, as recently shown for meriolin 16, derivative 3e was able to induce apoptosis in the Jurkat cells overexpressing the antiapoptotic protein Bcl-2. Since tumor cells often inactivate the intrinsic mitochondrial apoptosis pathway (e.g., by overexpression of Bcl-2), these meriolin congeners represent promising therapeutic agents for overcoming therapeutic resistance.